Pharmacist's role in HIV care in France. Implication for clinical improvement of people living with HIV worldwide. Issue 5 (9th September 2020) - Jacomet, Christine; Langlois, Julie; Secher, Solene; Coban, Dilek; Lambert, Celine; Zucman, David; Trout, Herve; Maarek, Rene; Billaud, Eric; Certain, Agnes
Abstract: In France, antiretroviral (ARV) treatment can be dispensed by hospital and/or community pharmacies. Since January 2016, an online patient medication file can be used to optimize dispensing, but medication interviews have not yet been incorporated into this system. To understand both people living with HIV (PLHIV) and their pharmacists' habits and expectations of patient medication file and interviews, two consecutive national surveys were organized. The first one, carried out in October 2016 in care centers, was an anonymous questionnaire for PLHIV. The second one was an online survey for community and hospital pharmacies conducted in February 2017. A total of 1137 PLHIV (68% men, of mean age 50.2 ± 11.5 years, CD4 count 671 ± 354, 90% with undetectable HIV viral load (VL) and 64.2% reporting comorbidities) and 246 pharmacies responded. While the existence of the online medication file is known by 58% of PLHIV, only 40% of pharmacists declare it to be systematically offered. It was offered to 120/694 (17%) PLHIV and 96 (80%) accepted it. Currently, 78 (7%) PLHIV feel well taken care of because they are offered medication interviews, 343/1078 (32%) would like to take advantage of this program, mainly those with a shorter ARV duration (OR ARV duration 0.97 [0.95‐0.99]), a VL less often undetectable (OR undetectable VL 0.55 [0.31‐0.98]), and those who feel anxious more often (OR anxious 2.38 [1.48‐3.84]). These results suggest that better implementation of medication files and interviews will strengthen current clinical pathways.